Metabolomic analysis of the effects of a mixed culture of Saccharomyces cerevisiae and Lactiplantibacillus plantarum on the physicochemical and quality characteristics of apple cider vinegar - Li, Ya-Nan; Luo, Yue; Lu, Zhen-Ming; Dong, Yan-Lin; Chai, Li-Juan; Shi, Jin-Song; Zhang, Xiao-Juan; Xu, Zheng-Hong (Frontiers in Nutrition, 2023)
This study compared differences in physicochemical characteristics of the vinegar made by a mixed culture (MC) of Saccharomyces cerevisiae and Lactiplantibacillus plantarum and a pure culture (PC) of Saccharomyces cerevisiae. Metabolomics analysis by Liquid Chromagraphy-Mass Spectrometry (LC-MS) was applied to the compositional differences between PC and MC vinegars, combined with quantification of organic acids, amino acids and B vitamins. A total of 71 differential metabolites including amino acids, organic acids and carbohydrates, and six possible key metabolic pathways were identified. MC enhanced the malic acid utilization and pyruvate acid metabolism during fermentation, increasing substrate-level phosphorylation, and supplying more energy for cellular metabolism. Higher acidity at the beginning of acetic acid fermentation, resulting from lactic acid production by Lactiplantibacillus plantarum in MC, suppressed the cellular metabolism and growth of Acetobacter pasteurianus, but enhanced its alcohol metabolism and acetic acid production in MC. MC vinegar contained more vitamin B, total flavonoids, total organic acids, amino acids and had a higher antioxidant capacity. MC enhanced the volatile substances, particularly ethyl lactate, ethyl caprate and ethyl caproate, which contributed to a stronger fruity aroma. These results indicated the mixed culture in alcoholic fermentation can effectively enhance the flavor and quality of apple cider vinegar.